Desenvolvimento de método utilizando a microextração líquido-líquido dispersiva em fase reversa para determinação de As, Cd, Hg, Pb, Co, Ni e V em excipientes farmacêuticos oleosos - Andriolli, Cristian Rafael (2021)
In this study, an extraction method using oily pharmaceutical excipients was developed for further determination of elemental impurity from classes 1(As, Cd, Hg, and Pb) and 2A (Co, Ni, and V) according to ICH Q3D. The evaluated sample preparation method was reversed-phase dispersive liquid-liquid microextraction (RP-DLLME). The determination of As, Cd, Pb, Co, Ni, and V was performed by inductively coupled plasma mass spectrometry (ICP-MS) and the Hg determination was by cold vapor generation (CVG) coupled to ICP-MS. The RP-DLLME method was performed by using a mixture of dispersant and extractant solvents, which were added directly to the sample. Some parameters such as dispersant solvent, proportion of dispersant and extractant solvents, extractant solvent concentration, extraction solution volume, sample mass, temperature, heating time, centrifugation time, stirring type, and time were evaluated. For all parameters evaluated, sample “A” was spiked with 1.0 μg g-1 of all analytes using oil standard solutions and the results were expressed in recovery (%). The optimized conditions of the proposed RP-DLLME method were: i) dispersant solvent: n-propanol; ii) proportion of dispersant and extractant solvents: 50:50% (v/v); iii) extractant solvent concentration and type: 3.0 mol L-1 HNO3 solution (As, Cd, Pb, Co, Ni e V) and 6.0 mol L-1 HCl solution (Hg); iv) extraction solution volume: 2.0 mL; v) sample mass: 5 g; vi) temperature: 85 °C; vii) centrifugation time: 10 min at 3450 rpm; viii) stirring type and time: 1.0 min by manual stirring. Accuracy was evaluated by comparing the results obtained by proposed method with those obtained by ICP-MS and CVG-ICP-MS after microwave-assisted wet digestion in a single reaction chamber (MAWD-SRC). No statistical difference (t-test, 95%) was observed between the results obtained for the elemental impurity from classes 1 and 2A after the RP-DLLME and MAWD-SRC methods. Accuracy was also evaluated by recovery experiments with the addition of all analytes at three concentrations levels (50, 100, and 150%) and according to the ICH Q3D recommendations for the parenteral route. The results for the analyte recovery experiments ranged from 94 to 100% with RSDs lower than 5%. The limits of detection for the proposed method were 0.014, 0.002, 0.001, 0.006, 0.002, 0.012, and 0.031 μg g-1 for As, Cd, Hg, Pb, Co, Ni, and V, respectively. The developed method was considered suitable for the determination of the elements of classes 1 and 2A in oily pharmaceutical excipients. The evaluation was carried out according to the twelve green chemistry principles using an Analytical GREEnness calculator, in order to evaluate how green a method can be considered. In this way, each variable is converted in a scale from 0 to 1 (resulting in a red, yellow, and green color scale). As a result, the proposed RP-DLLME method was considered greener than the MAWD-SRC method, obtaining as general scores 0.49 and 0.35, respectively. The main advantages of the proposed method include simplicity of operation, low amount of residues generation, use of high sample mass, and high throughput. The proposed approach is the first application of a RP-DLLME method combined with ICP-MS and CVG-ICP-MS determination for pharmaceutical samples.